Da regulamentação à implementação do processo judicial eletrônico na Justiça Eleitoral do Tocantins: a (des)uniformização na implantação e operacionalização do processo judicial eletrônico e o comprometimento do acesso à justiça e à concretização dos direitos políticos - Aglantzakis, Vick Mature Aglantzakis (Universidade Federal do Tocantins, 2021)
The technological revolution conformed in the use of electronic systems for the processing of judicial proceedings in the Brazilian Judiciary Courts has occurred at different times, in an asynchronous way, through different platforms, which end up promoting a myriad of various procedures of access and operability, often generating disuniformization in the process of implementation and operationalization of the systems used, compromising the judicial provision and access to justice. Such situations are evident in the course of the implementation of the PJe in the Electoral Justice and are embodied in the research that resulted in this dissertation that aims to understand the context and causes that hinder the effective standardization of the electronic judicial process, in addition to its implementation, mainly contemplating the operability of the PJe system by the servers that use it. Thus, considering the need for a precise delimitation and the professional nature of the research undertaken in the Professional Master's Degree, the research locus took place in the Regional Electoral Court of Tocantins, which participated in the process of implementation of the PJe system from the initial moment of discussions in the Superior Electoral Court, for the implementation of the system of electronic processing of judicial proceedings. Based on the professional experience of the researcher and the use of a qualitative approach, based on a plural methodology, conformed to the principles of interdisciplinary research, this dissertation synthesizes possibilities of solutions that can be taken internally by the Regional Electoral Court of Tocantins to improve the operability of the system by the servers, promoting fluid uniformity, which adapts to the internal needs and the moment that must be carried out, thus realizing the principles that guide the Public Administration, as well as permanently improving the judicial provision and access to justice aimed at guaranteeing their own fundamental rights, the full rights of citizenship, embodied in the active and passive political rights of the citizen.